ASSOCIATION BETWEEN ATP1A1 GENE POLYMORPHISMS WITH SEMEN CHARACTERISTICS IN HOLSTEIN BULLS - S. M. Eidan; S. A. Khudhir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to identify the polymorphism of ATP1A1 gene, distribution ratios, and its association with semen characteristics of Holstein bulls. Twenty-five Holstein bulls were used currently. Blood samples were collected via venipuncture to separate the DNA and identify the polymorphism of the ATP1A1 gene. Semen was collected using an artificial vagina for fresh evaluation. Results were showed the change of cytosine (C) nucleotide at site 15738 to adenine (A) at the exon 17 (SNP C15738A) of the ATP1A1 gene. Two polymorphisms were obtained according to this change, the first is wild (CC; allele frequency 0.84), and the second is heterogeneous (CA; allele frequency 0.16). The CC polymorphism of the ATP1A1 gene exhibited a highly significant (p